(untitled) (Bangladesh Journal of Otorhinolaryngology, 2014)
Objectives: To find out the pattern of complications, frequency, risk factors and the management after total laryngectomy. Methods: It was a cross sectional study done in the Department of Otolaryngology & Head- Neck Surgery, Shaheed Suhrawardy Medical College Hospital, Dhaka from July 2007 to Dec 2009. 15 patients undergoing total laryngectomy for histologically proven Carcinoma larynx were included in this study. Patients were reviewed after surgery and any complication that occurred was recorded. The presentation, diagnosis and management of these complications were discussed after total laryngectomy. Results: There were 15 male patients, 3 non radiated cases and 12 post irradiated cases. Age of patients ranged from 35-75 years. Complications included wound infection (04), pharyngocutaneous fistula (03), flap necrosis (01), pharyngeal stenosis (01), stomal stenosis (01) and stomal recurrence (01). Conclusions: Wound infection and pharyngocutaneous fistula are most common complications after total laryngectomy. Preoperative radiotherapy is an important risk factor for development of pharyngocutaneous fistula in total laryngectomy patients. DOI: http://dx.doi.org/10.3329/bjo.v19i2.16366 Bangladesh J Otorhinolaryngol 2013; 19(2): 82-86